1991
DOI: 10.1080/10503309112331334061
|View full text |Cite
|
Sign up to set email alerts
|

The psychotherapeutic value of a “Chat”: A verbal response modes study of a placebo attention control with breast cancer patients

Abstract: In a randomized controlled trial of breast cancer patients awaiting surgery, 51 client-centered psychotherapeutic interventions and 56 "chats" were analyzed using Stiles' Verbal Response Modes (VRMs). The 30-minute interventions and chats were carried out the night before surgery by a consultant surgeon trained in client-centered counseling techniques. Significant differences in therapist and client VRMs were found between interventions and chats. Therapist reflection and acknowledgment were the predominant VR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Finally, Burton, Parker, and Wollner (1991) found that breast cancer patients about to undergo surgery, who met in a single 45-minute preoperative interview with their surgeons, had less distress about body image, less anxiety, and less depression. They also were better at a 1-year follow up than control participants who did not have the interview.…”
Section: Self-expressionmentioning
confidence: 96%
“…Finally, Burton, Parker, and Wollner (1991) found that breast cancer patients about to undergo surgery, who met in a single 45-minute preoperative interview with their surgeons, had less distress about body image, less anxiety, and less depression. They also were better at a 1-year follow up than control participants who did not have the interview.…”
Section: Self-expressionmentioning
confidence: 96%
“…However, designing appropriate attention-placebo conditions for behavioral interventions may be challenging. A study that used a 30-minute “chat” about issues unrelated to patients’ illness to control for the attention of a brief psychotherapeutic intervention found that it appeared to have some therapeutic value 33, 34. Similarly, meeting repeatedly with an empathetic research assistant over the course of data collection unintentionally led some participants to report that they felt as if they had received an intervention 8.…”
Section: Participant Disappointment Regarding Treatment Group Assignmentmentioning
confidence: 99%
“…Assessing actual session contents might shed light not only on the course favorites and close finishes, but also on another important result of horserace research, the surprising (to some) effectiveness of intended "placebos" involving client-therapist contact. For example, a process analysis by Burton, Parker, and Wollner (1991) showed how participants in a "chat" control for a client-centered intervention with mastectomy patients systematically addressed psychologically important issues in ways that could account for their equivalently beneficial outcomes.…”
Section: Stiles Shapiro and Barkhammentioning
confidence: 99%